2015
DOI: 10.1016/j.molcel.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Signaling Mechanism Revealed from a Stem/Progenitor Cell Cistrome

Abstract: SUMMARY Thousands of cis-elements in genomes are predicted to have vital functions. While conservation, activity in surrogate assays, polymorphisms, and disease mutations provide functional clues, deletion from endogenous loci constitutes the gold-standard test. A GATA-2-binding, Gata2 intronic cis-element (+9.5) required for hematopoietic stem cell genesis in mice is mutated in a human immunodeficiency syndrome. As +9.5 is the only cis-element known to mediate stem cell genesis, we devised a strategy to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 72 publications
2
84
0
Order By: Relevance
“…One plausible explanation for the difference in SCL occupancy is that differences in undesignated sequences in the composite E-box–GATA motif may influence complex formation, depending on whether GATA1 or GATA2 is present. Binding analyses utilizing naked DNA have indicated that SCL preferentially binds to CAGGTG (33) or CAGATG (42) motifs in essential hematopoiesis genes, whereas CATCTG sequences are enriched in GATA2-occupied loci in lineage-negative hematopoietic progenitors (43). Furthermore, the spacer lengths and sequences between E-box and GATA-binding motif vary at individual loci.…”
Section: Composite Elements With An E-box and A Gata-binding Motifmentioning
confidence: 99%
“…One plausible explanation for the difference in SCL occupancy is that differences in undesignated sequences in the composite E-box–GATA motif may influence complex formation, depending on whether GATA1 or GATA2 is present. Binding analyses utilizing naked DNA have indicated that SCL preferentially binds to CAGGTG (33) or CAGATG (42) motifs in essential hematopoiesis genes, whereas CATCTG sequences are enriched in GATA2-occupied loci in lineage-negative hematopoietic progenitors (43). Furthermore, the spacer lengths and sequences between E-box and GATA-binding motif vary at individual loci.…”
Section: Composite Elements With An E-box and A Gata-binding Motifmentioning
confidence: 99%
“…Insufficient GATA-2 levels/activity resulting from GATA2 coding or +9.5 enhancer mutations underlie hematologic diseases including primary immunodeficiencies that frequently progress to myelodysplastic syndrome (MDS), acute myeloid leukemia (AML) (Dickinson et al, 2011; Hahn et al, 2011; Hsu et al, 2011; Ostergaard et al, 2011) and pediatric MDS/AML independent of immunodeficiency (Wlodarski et al, 2016). Since GATA factor occupancy of a GATA motif in chromatin does not predict GATA factor-dependent regulation of the linked gene (DeVilbiss et al, 2014; Hewitt et al, 2015; Sanalkumar et al, 2014), many questions remain unanswered regarding mechanisms conferring GATA-2 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Prioritization of GATA-2-occupied E-box-GATA elements with attributes resembling the +9.5 enhancer, and gene editing in G1E mouse erythroid precursor cells revealed sites that regulate their endogenous loci and seemingly similar sites that do not (Hewitt et al, 2015; Tanimura et al, 2015). The functional sites included a conserved intronic enhancer (Samd14-Enh) at the largely unstudied, GATA-2-occupied Samd14 gene (Hewitt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations